The Value of a Liberal Arts Degree: Students' Perspectives on Financial and Nonfinancial Returns on Investment. Issue 5 (20th October 2022) - Barrett, Laura; Helens-Hart, Rose
Abstract : This study explores student perceptions of the financial and nonfinancial return on investment (ROI) of a liberal arts (LA) degree through surveys and interviews. Four prominent returns emerged through qualitative analysis of data: financial security, a credential, personal growth, and the promise of meaningful work. Results demonstrated the influence of anticipatory socialization on conceptions of meaningful work and the ROI of the LA degree. These findings detail a contemporary view of the value of a LA degree in the United States and are important for educators and administrators who seek to transition students from college to career.